2018
DOI: 10.3390/su11010077
|View full text |Cite
|
Sign up to set email alerts
|

Family Business Owner as a Central Figure in Customer Relationship Management

Abstract: This paper presents theoretical and empirical research on the activities and attitudes of a family business owner regarding marketing as a business function. The development of successful business relationships of a family business is tightly connected with the activities of the business owner. The theoretical review examined numerous family and non-family business studies by analyzing the existing paradigms of marketing management as a whole. The empirical research, surveying 420 family businesses in Serbia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
1
14
0
5
Order By: Relevance
“…Administrative innovation is understood as a set of activities involving changes in organisational structures or administrative processes, such as human resource policies for recruitment and allocation, task assignation and reward policies (Gopalakrishnan & Damanpour, 1997). Innovation in production and IT processes favours an ambidextrous performance, whereas changes in logistics systems, despite being positive, are less relevant (Arsi c et al, 2018).…”
Section: Crm and Customer Knowledge Managementmentioning
confidence: 99%
“…Administrative innovation is understood as a set of activities involving changes in organisational structures or administrative processes, such as human resource policies for recruitment and allocation, task assignation and reward policies (Gopalakrishnan & Damanpour, 1997). Innovation in production and IT processes favours an ambidextrous performance, whereas changes in logistics systems, despite being positive, are less relevant (Arsi c et al, 2018).…”
Section: Crm and Customer Knowledge Managementmentioning
confidence: 99%
“…Findings from various studies have justified the need of CRM for long-term business sustainability (Siu 2016). Prior studies have generally found a positive relationship between implementation of the CRM system and company performance (Arsić et al 2019), or (Siu 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the IT system, the CRM is defined as an IS that supports the work of marketing, sales, service or contact centre departments. According to Xu et al, "CRM is an information industry term for methodologies, software, and usually Internet A lot of studies show that the CRM system has a positive impact on organizational effectiveness and performance (Elmuti et al, 2009;Reimann et al, 2010;Arsi´c et al, 2019). Some researchers consider the CRM in the context of the sales strategy (Barone and DeCarlo, 2012) or focus only on the CRM impact on sales performance (Weinstein and Mullins, 2012;Deeter-Schmelz, 2018) or sales managers effectiveness in the context of resource orchestration (Badrinarayanan et al, 2019).…”
Section: Impact Of the Crm On Organizational Effectiveness And Performentioning
confidence: 99%